The effect of transformational leadership on subordinate’s self-efficacy / Diyana Rahmat and Nurhafizah Mohd Salleh - Rahmat, Diyana; Mohd Salleh, Nurhafizah (Faculty of Business and Management, 2013)
This research is all about “The Effect of Transformational Leadership on Subordinate’s Self-Efficacy”. In this era globalization, environment always changes. This means that the culture of working environment will always change. In this study, the researcher will study about the transformational-transactional leadership either there are the positive or negative effect with the subordinate self-efficacy. Otherwise, the researcher also wants to explore which one of transformational element and contingent reward that gives high positive relationship to the subordinate self-efficacy. If the result is positive, it shows the transformational leadership give high impact to the subordinate self-efficacy. The researcher will explain more in chapter 4 and 5 which there have the result of this study. Besides that, the researcher will elaborate more and also analyse the data in chapter 4 and 5.